Associations Between Sputum Torque Teno Virus Load and Lung Function and Disease Severity in Patients With Chronic Obstructive Pulmonary Disease - Xie, Yu; Xue, Qing; Jiao, Weike; Wu, Jianhui; Yu, Yan; Zhao, Lili; Xu, Yu; Deng, Xinyu; Fang, Guiju; Zheng, Yali; Gao, Zhancheng (Frontiers in Medicine, 2021)
Purpose: Viral load of Torque Teno virus (TTV) is elevated in immunosuppressed patients. The weakened immune response is typical in chronic obstructive pulmonary disease (COPD) patients. However, the relationship between TTV and COPD is still unknown. Patients and Methods: We enrolled 91 patients admitted to hospitals with acute exacerbation of COPD (AECOPD) between January 2017 and August 2017 (ClinicalTrials.gov ID, NCT03236480). Sputum samples were gathered during hospitalization and the 120-day follow-up. TTV distribution and genogroups were assessed, and the associations between viral loads and clinical parameters were analyzed. Results: TTV DNA was detected in 95.6% of COPD patients, and the viral load was nearly invariable at the stable and exacerbation states. Most TTV DNA-positive patients carried four distinct genotypes. Sputum load of TTV was positively associated with RV/TLC (r = 0.378, p = 0.030), and negatively correlated with FEV1/pre and FEV1/FVC (r = −0.484, −0.432, p = 0.011, 0.024, respectively). Neutral correlation between the TTV DNA load and COPD assessment test (CAT) scores (r = 0.258, p = 0.018) was observed. Conclusion: Sputum loads of TTV DNA could be a novel indicator for lung function and disease severity assessment in COPD patients.